The rare hemoglobin variants Hb O-Arab and Hb D-Punjab identified in population-based genetic screening throughout Guangxi, China - Gui, Chunrong; Cheng, Zifeng; Chen, Yongsheng; Ma, Yunting; Chen, Hongfei; Wei, Wei; Wei, Xianda; Liu, Juliang; Zhou, Xu; Du, Qianqian; Lai, Yinghui; Gui, Baoheng (Frontiers in Genetics, 2025)
BackgroundHemoglobinopathies are a group of autosomal recessive disorders characterized by a high degree of clinical and genetic heterogeneity. Comprehensive genetic screening for hemoglobin variants is crucial for prevention and treatment of these conditions. Single-molecule real-time (SMRT) sequencing enables efficient and reliable analysis of common and complex or rare hemoglobin variants.MethodsWe launched a population-based genetic screening program for hemoglobinopathies in Guangxi, China, using SMRT. The in silico structural predictions based on Alphafold2 were performed for the rare variants identified. Additionally, a comprehensive literature review was conducted to elucidate the origin and genotype-phenotype correlation of these variants.ResultsA total of 11,019 participants throughout Guangxi were recruited via the screening program. In two unrelated families, the variants, Hb O-Arab and Hb D-Punjab at the same genetic locus, were identified with an extremely low frequency of 0.0045% [1/(11,019*2), respectively] in the population. Structural prediction showed Hb O-Arab exerted a relatively significant impact on the hemoglobin structure, whereas the influence of Hb D-Punjab was minimal. This was consistent with findings from the literature review and the two recruited families, which confirmed that individuals with Hb O-Arab presented relatively obvious manifestations compared to those with Hb D-Punjab.ConclusionTwo rare variants, Hb O-Arab and Hb D-Punjab, were identified in Guangxi, China using SMRT. The first report of Hb O-Arab enriches the spectrum of hemoglobin variants in the Chinese population. Analyzing the frequency, origin and genotype-phenotype correlation of these variants could pave the way for clinical management and genetic counseling for hemoglobinopathies.